Elements of a unified prognostic model for secondary air contamination by resuspension. - Besnus, F.; Garger, E.; Gordeev, S.; Hollander, W.; Kashparov, V.; Martínez-Serrano, José Javier; Mironov, V.; Nicholson, K.; Tschiersch, J.; Vintersved, I. (Office for Official Publications of the European Community, 1996)
Based on results of serveral joint experimental campaigns and na extensive literature survey, a progostic model was constructed capable of predicting airborne activity concentrations and size distributions as well as soil surface activity concentrations as a function of time and meteorological conditions. Example scenario calculations show that agricultural practices are of lesser importance to secondary air contamination than dust storms inmediately after primary deposition and forest fires
Keywords: Contaminación radiactiva; Reactores nucleares - Accidentes - 1986; Atmósfera - Contaminación radiactiva; Accidentes nucleares; Chernobyl (Ucrania) - Accidentes nucleares - 1986; Model; Resuspension; Air contamination; Chrenobyl